Delinquency of Constitutional Court Decision Number 90/PUU-XXI/2023 on Age Limit Requirements for Presidential and Vice Presidential Candidature - Juanda; Nina Zainab (Siber International Journal of Advanced Law (SIJAL), 2024)
The Constitutional Court is an institution of judicial power which has a judicial function to uphold law and justice. Law Number 24 of 2003 explains that the duties and functions of the Constitutional Court are to handle constitutional cases regarding certain constitutional matters in order to safeguard the constitution so that it is implemented responsibly in accordance with the will of the people and democratic ideals. One of the powers of the Constitutional Court is the authority of "judicial review", namely the authority to review laws where the decisions are final and binding. This authority is very important because it is a legal corridor and a way for citizens to defend their constitution. If there is a conflicting law, they can request it to be cancelled, but on the one hand, this authority is so large that in maintaining the constitution, constitutional judges are certainly needed who have knowledge and expertise. state administration and commitment to implementing and monitoring it in accordance with the corridors of the constitution, so that every decision that is issued does not go outside the corridors so that the constitution itself is constitutionally maintained. This research was written using normative juridical methods and was based on current phenomena. The results obtained are the importance of the role of the Constitutional Court in handing down decisions because the Constitutional Court's decisions are final and have binding legal force. Judges must have high integrity, be independent and free from any influence. The public and state administrators must be able to restore the dignity of the Constitutional Court by starting with the recruitment of constitutional judges and ensuring that the functions and authority of the Constitutional Court run in accordance with the ideals of its formation.